Genetics of hairy cell leukemia - Jorge J. Nieva (Frontiers Media S.A., 2011)
Hairy cell leukemia (HCL) is a chronic B-cell lymphoproliferative disorder characterized by cytopenias, splenomegaly, and bone marrow fibrosis associated with an infiltrate of B-lymphocytes. Although in the majority of cases diagnosis and treatment of the disease is relatively straightforward, there is a lack of clinical and molecular data on its genetic mechanisms. Recent advances in gene expression profiling have identified a number of proteins that are specific to the HCL phenotype. However, these data are only the first step in identifying the genetic event responsible for development of the disease. Because of the success of purine analog therapy in treating the disease, there has so far been little interest within the scientific community in gaining a greater understanding of the genetics that drive the neoplastic clone in this strikingly homogeneous and well characterized clinical entity. This review describes the epidemiological genetic and molecular events associated with HCL.